Towards vegetation species discrimination by using data-driven descriptors - Nogueira, Keiller; Dos Santos, Jefersson A.; Fornazari, Tamires [UNESP]; Freire Silva, Thiago Sanna [UNESP]; Morellato, Leonor Patrícia Cerdeira [UNESP]; Torres, Ricardo Da S. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
In this paper, we analyse the use of Convolutional Neural Networks (CNNs or ConvNets) to discriminate vegetation species with few labelled samples. To the best of our knowledge, this is the first work dedicated to the investigation of the use of deep features in such task. The experimental evaluation demonstrate that deep features significantly outperform wellknown feature extraction techniques. The achieved results also show that it is possible to learn and classify vegetation patterns even with few samples. This makes the use of our approach feasible for real-world mapping applications, where it is often difficult to obtain large training sets.
Keywords: Deep Learning; Feature Learning; High-resolution Images; Image Classification; Machine Learning; Remote Sensing